The Spatial Patterns of Pacenan House in Sumberejo, Situbondo - Taufik Hidayat; Yusfan Adeputera Yusron; Susilo Kusdiwanggo (Jurnal Indonesia Sosial Teknologi, 2024)
Pacenan house is a traditional house of the coastal area in Situbondo. The architectural style of Pacenan house is adapted from Tanean lanjhang traditional house. The spatial pattern of Pacenan house differs from that of Tanean Lanjhang, as Pacenan house only has "roma" (rooms) and "amper" (open spaces). However, over time, the spatial patterns of Pacenan house have transformed. Therefore, this study was conducted to identify the transformations in spatial patterns and their impact on the building shapes of Pacenan houses in Sumberejo, Situbondo. Research data was obtained through field observations and interviews. The data was then analyzed descriptively. The results indicate changes in spatial patterns occurring in Pacenan houses in the village of Sumberejo, including the addition of rooms and alterations in the function of spaces. Transformations in spatial patterns are influenced by space requirements, land availability, social factors, and economic considerations. The impact of these changes in spatial patterns varies; some result in alterations to the building's form, while others do not transform the structure.